2017
DOI: 10.1002/ijc.31008
|View full text |Cite
|
Sign up to set email alerts
|

Low folate metabolic stress reprograms DNA methylation‐activated sonic hedgehog signaling to mediate cancer stem cell‐like signatures and invasive tumour stage‐specific malignancy of human colorectal cancers

Abstract: The mechanistic role of colonic low folate metabolic stress (LFMS) in colorectal cancer (CRC) malignancy development remains unknown. Folate analysis on the 99 paired human CRC tissues localized LFMS to the deep invasive T3/T4 staged tumours with hypo-methylated sonic hedgehog (Shh) promoter region and amplified expressions of Shh ligand and Gli1 effector, which coincided with deregulated expressions of the epithelial-mesenchymal transition (EMT) mediators. Colonic folate levels of CRC were inversely correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…Dissimilarities was observed in previous study, compared with our results, which might be the uniformity of definition and isolation techniques for CSCs [46]. In addition, the origins of CSCs within a cancer have not been clarified, oncogenic transformation from progenitor cells or normal tissue stem cells might be one of possible mechanisms [14], which might be accompanied with abnormal nucleic acid metabolism, such as DNA methylation [47] or RNA expression [48]. Moreover, one of the most important issues about cancer therapy is that increasing evidence has shown chemotherapeutic resistance in cancers, which is considered partially due to the existence of CSCs [14].…”
Section: Discussionsupporting
confidence: 54%
“…Dissimilarities was observed in previous study, compared with our results, which might be the uniformity of definition and isolation techniques for CSCs [46]. In addition, the origins of CSCs within a cancer have not been clarified, oncogenic transformation from progenitor cells or normal tissue stem cells might be one of possible mechanisms [14], which might be accompanied with abnormal nucleic acid metabolism, such as DNA methylation [47] or RNA expression [48]. Moreover, one of the most important issues about cancer therapy is that increasing evidence has shown chemotherapeutic resistance in cancers, which is considered partially due to the existence of CSCs [14].…”
Section: Discussionsupporting
confidence: 54%
“…Folate is known to play an important role in human health and disease due to its participation in diverse metabolic pathways as well as in the regulation of methylation reactions. Pleiotropic effects of folate in cancer cells have been linked to migratory capacity and invasiveness; though effects may differ by cancer type, stage and molecular subtype [50,61,62]. We have previously shown that folic acid withdrawal resulted in metabolic and bioenergetic changes indicative of a less proliferative as well as less migratory phenotype in mouse TNBC cell lines [50].…”
Section: Discussionmentioning
confidence: 99%
“…Altered folate metabolism has indeed been implicated in promoting cancer stem cell formation. For example, low folate was linked to pluripotent gene expression via sonic hedgehog or Akt-mTOR-HIF1-FOXO3a pathways in colorectal 30 and lung cancer 31 . Similarly, 5-MethylTetraHydroFolate down-regulation was observed during reprogramming of mouse embryonic fibroblasts (MEFs) into mouse induced pluripotent cells (iPSC) 32 .…”
Section: Discussionmentioning
confidence: 99%